2016
DOI: 10.1039/c6ce01360k
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and structural remarks on malonate-based lanthanide coordination polymers

Abstract: The synthesis, structural and thermal studies of several malonate-containing lanthanide(iii) complexes plus a structural overview of twenty-three known homometallic Ln(iii)-malonate systems are provided herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 77 publications
3
17
1
Order By: Relevance
“…In the DSC plot an endotherm at about 150°C corresponds to the dehydration step, while the exotherms at about 300 and 410°C represent the combustion of the malonate ligands. The shapes of the TGA curves for 1 – 5 are similar to those of the other malonate-containing Ln 3+ complexes described in the literature (Muraishi et al, 1991; Doreswamy et al, 2003; Chrysomallidou et al, 2010; Delgado et al, 2016) suggesting that the stability of the complexes is comparable to the reported ones.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…In the DSC plot an endotherm at about 150°C corresponds to the dehydration step, while the exotherms at about 300 and 410°C represent the combustion of the malonate ligands. The shapes of the TGA curves for 1 – 5 are similar to those of the other malonate-containing Ln 3+ complexes described in the literature (Muraishi et al, 1991; Doreswamy et al, 2003; Chrysomallidou et al, 2010; Delgado et al, 2016) suggesting that the stability of the complexes is comparable to the reported ones.…”
Section: Resultssupporting
confidence: 84%
“…Lanthanide(III) ions are hard Lewis acids and prefer to combine with hard Lewis bases such as oxygen donors (Bünzli, 2014). On the basis of this fact, carboxylate ligands have been widely applied for the preparation of lanthanide coordination polymers (Hansson, 1973a,b; Wenmei et al, 1992; Marrot and Trombe, 1994; Benmerad et al, 2000; Hernández-Molina et al, 2000, 2002, 2003; Doreswamy et al, 2003, 2005; Thirumurugan and Natarajan, 2004; Cui et al, 2005; Yan et al, 2005; Cañadillas-Delgado et al, 2006; Deacon et al, 2006; Rahahlia et al, 2007; Zhang et al, 2007; Fang et al, 2008; Wang et al, 2009; Chrysomallidou et al, 2010; Silva et al, 2010; Jin et al, 2012; Seidel et al, 2012; Sharif et al, 2012; Calahorro et al, 2013; Tian et al, 2013; Bünzli, 2014; Delgado et al, 2016; Li et al, 2017). The flexible aliphatic dicarboxylates (e.g., malonate and succinate) are more fascinating than the rigid mono or aromatic carboxylates due to many possible conformations (Cui et al, 2005; Rahahlia et al, 2007; Wang et al, 2009; Delgado et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,10,16,[33][34][35] Lanthanide(III) ions have high affinity towards hard bases, such as oxygen donors and in this respect multicarboxylate ligands, which possess hard base sites of high density, seem to be ideal ligands in the construction of MOFs. [3][4][5]8,11,15,16,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Among these ligands, the rigid carboxylates, benzene-1,4-dicarboxylic acid (Bdc-H 2 ) 4, [34][35][36][37][38] and its derivatives with a centrosymmetric structure 3,5,9,35,[38][39][40][41][42][43] have drawn considerable attention because they possess various coordination modes such as, monodentate, bis-monodentate, bidentate, tridentate and chelating bridging; which favor the bui...…”
Section: Introductionmentioning
confidence: 99%